Apoptosis induction of Newcaastle disease virus strain AF2240 on mouse myelomonocytic leukaemia (WEHI-3B) and human promyelocytic leukaemia (HL60) cells - Siti Aisyah Abu Bakar
Newcastle Disease Virus (NDV) an avian paramyxovirus, is a virus that causes a disease of domestic poultry and wild birds characterized by gastro-intestinal, respiratory and nervous signs. NDV is considered to be a very promising oncolytic agent which has been used in a clinical setting as an experimental oncolytic agent for more than 30 years. Several strains of NDV were reported to induce cytolysis and have apoptosis-inducing properties againts various cancer cell lines. The cells exposed to this virus will trigger apoptosis and result in cell death. In Malaysia, the oncolytic effects of two NDV isolates, AF2240 and V4-UPM have been studied on several cancer cell lines. However, NDV AF2240 has not yet been sufficiently investigated on leukemic cells. Thus, the oncolytic and apoptotic effect of NDV AF2240 on mouse myelomonocytic leukaemia, WEHI-3B and human promyelocytic leukaemia, HL60 cells were investigated in this study. We found that NDV strain AF2240 is cytolytic to both cells. Result from MTS, [3-(4,5-dimethylthiazol-2-yl)-5-(3carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium]cytolytic assay showed that CD50 for NDV AF2240 against WEHI-3B and HL60 were 0.7 and 130 HAU, respectively. The cell death via apoptosis observed in AO/PI assay was 42.67+- 1.76 and 36.12+-4.32% of apoptotic cells which were detected in WEHI-3B and HL60 cells respectively after 72 hours of treatment with NDV AF2240. The result were in agreement with Annexin V-FITC where NDV AF2240 has been demonstrated to kill both cell lines via apoptosis. In addition, a ladder-like pattern (typical character of DNA cleavage between nucleosomes) was visible in treated cells, which is a hallmark of apoptosis. DNA damages in the individual cells were detected by using comet assay at 2 hours post-treatment with NDV AF2240 in a concentration dependent manner. The mechanism of apoptosis through activation of induced by NDV AF2240 was also analysed. The result suggest that apoptosis in NDV-infected tumor cells is dependent on caspase as both initiator caspases, caspase 8 (extrinsic death receptor pathway) and caspase 9 (instrinsic mitochodria pathway) were activated. Activation of caspase 3/7 were also detected in the cells treated with NDV AF2240. Furthermore, apoptosis by NDV AF2240 was effectively inhibited by ZVAD-FMK indicate that NDV AF2240-induced apoptosis is entirely dependent on caspase activation.